The Future Potential of Cryopreservation for Assisted Reproduction - Song, Ying (2009)
Cryopreservation of human gonadal tissue and oocytes has brought about new and exciting research in reproductive medicine, as well as new cryopreservation techniques that are dramatically improving post-thaw viability and freezing damage. The work done on gonadal tissues is aimed at improving the quality of life for infertile patients and for prepubertal patients undergoing gonadotoxic chemotherapy, patients for whom hormonal stimulation /IVF is not an option, and women without partners. Cryopreservation of mature oocytes is the best model for timing IVF. Vitrification is likely to benefit the field, and since 2005, implantation and pregnancy rates from vitrified oocytes have matched or eclipsed results from conventional methods, due to new cell-specific methods and formulas. Cryopreservation of immature oocytes leads to a new direction of egg banking in future. Preserving ovarian tissue for autografting is still promising and has resulted in folliculogenesis, resumed hormone production and live births in limited cases. The use of small cortical blocks, or mechanical/chemical digestion of ovarian tissue for isolation of follicles is a new direction for ovary preservation for reasons of cryoprotectant permeation and graft revascularization. Maturation of follicles in vitro has become more feasible with the use of alginate microencapsulation. Testicular tissue preservation has taken a sharp turn towards preservation of gonadal stem cells. Research into the mechanism for spermatogenesis points to the ability for male germ cells to resume spermatogenesis. The cryopreservation of minced testicular tissue for isolation of germ cells via chemical digestion has produced viable cells, however structural damage that may be avoided by vitrification has been noted to the surrounding cell junctions and supporting cells.